Ground improvement constructions with particular reference to stone column (case study : electrified double track project between Rawang and Ipoh) / Masfarizan Maslan - Maslan, Masfarizan (2003)
The use of ground improvement is to increase bearing capacity, settlement control, lateral stability which has proven to be a cost effective improvement subsoil compare to the pile embankment system. The stone column method is one of the ground improvement works. The Electrified Double Track Project between Rawang and Ipoh has been choose as a case study. Vibro replacement with stone column is a subsoil improvement method at which large sized columns of coarse backfill material install in the soil by means of special depth vibrators.